Relevansi Badan Khusus dalam Penanganan Sengketa Pemilihan Umum Kepala Daerah di Indonesia - Sulistyowati, Sulistyowati; Dewi Nadya Maharani; Indri Palindangan; Gusti Bintang Maharaja (UNES Law Review, 2024)
Election dispute management is a vital element in maintaining the integrity of the democratic process in Indonesia. Electoral conflicts can arise at various stages, from the nomination process, campaigning, voting, to the determination of election results. Therefore, it is very important to have an effective and fair mechanism to resolve such disputes. This study examines the mechanisms and institutions involved in the resolution of electoral disputes in Indonesia. Reviewing the development of regulations related to election disputes and efforts to improve the system that has been done, including the role of the Constitutional Court, the election supervisory board, and the General Election Commission. The author uses qualitative research methods by collecting data from various literature sourced from the internet. This study aims to provide a comprehensive overview of how to resolve electoral disputes, as well as to identify challenges and opportunities in the improvement of the electoral dispute resolution system. With a better understanding of existing mechanisms and regulations, it is expected to increase public confidence in the electoral process and strengthen democracy in Indonesia. This study evaluates various efforts that have been made to improve the electoral dispute resolution system, such as regulatory reform, capacity building of related institutions, and community participation in overseeing the electoral process. Thus, it is expected that the results of this study can contribute significantly to the development of the democratic system in Indonesia.